Analisis Dampak Fintech Syariah Terhadap Ingklusi Keuangan Masyarakat di Desa Pagar Kecamatan Ulu Talo Kabupaten Seluma - N, Nopiah; Harpuri, Pupu; Hasanah, Uswatun (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the impact of sharia fintech usage on financial inclusion in the community of Pagar Village, Ulu Talo District, Seluma Regency. Sharia fintech is a financial technology innovation based on sharia principles that is expected to extend community access to financial services, especially in rural areas. This study uses a quantitative approach with a survey method, where data were collected through the distribution of questionnaires to 50 respondents selected using purposive sampling technique. Data analysis was conducted using multiple linear regression, t-test for partial testing, F-test for simultaneous testing, and the coefficient of determination (R) to determine the extent of the independent variables' influence on the dependent variable. The results indicate that the variables of sharia fintech literacy, service access, and community trust have a significant partial effect on financial inclusion. It shows that the variables of sharia fintech literacy, access to services, and public trust significantly influence financial inclusion partially. This research concludes that sharia fintech plays an important role in enhancing financial inclusion in rural communities.